ENT 600 : SharpSafer Bin / Aslina Abdul Samar … [et al.] - Abdul Samar, Aslina; Asmungin, Hasliza; Suhari, Rohaini; Pardi, Siti Nur Hazira; Mohd Rasip, Nur Aqilah; Mohd Ansari, Saminah Begum (2016)
The innovation is a SharpSafer Bin. The team was decided to design a sharp bin attach with digital weigh scale. This sharp bin very convenience for busiest ward at the hospital because they will alert when this sharp bin reach their limit, alarm will trigger to inform them that they must change and discard the sharp bin. Nowadays cases of needle stick injury were increase among health care worker staff. This is due to poor management of handling of sharp bin among the staff. Hospital also must provide high quality of sharp bin to make sure it is safe to support the sharp material.